The National Health and Resilience in Veterans Study: A Narrative Review and Future Directions - Fogle, Brienna M.; Tsai, Jack; Mota, Natalie; Harpaz-Rotem, Ilan; Krystal, John H.; Southwick, Steven M.; Pietrzak, Robert H. (Frontiers in Psychiatry, 2020)
United States (U.S.) veterans are substantially older than their non-veteran counterparts. However, nationally representative, population-based data on the unique health needs of this population are lacking. Such data are critical to informing the design of large-scale outreach initiatives, and to ensure the effectiveness of service care delivery both within and outside of the Veterans Affairs healthcare system. The National Health and Resilience in Veterans Study (NHRVS) is a contemporary, nationally representative, prospective study of two independent cohorts (n = 3,157 and n = 1,484) of U.S. veterans, which is examining longitudinal changes, and key risk and protective factors for several health outcomes. In this narrative review, we summarize the main findings of all NHRVS studies (n = 82) published as of June 2020, and discuss the clinical implications, limitations, and future directions of this study. Review of these articles was organized into six major topic areas: post-traumatic stress disorder, suicidality, aging, resilience and post-traumatic growth, special topics relevant to veterans, and genetics and epigenetics. Collectively, results of these studies suggest that while a significant minority of veterans screen positive for mental disorders, the majority are psychologically resilient. They further suggest that prevention and treatment efforts designed to promote protective psychosocial characteristics (i.e., resilience, gratitude, purpose in life), and social connectedness (i.e., secure attachment, community integration, social engagement) help mitigate risk for mental disorders, and promote psychological resilience and post-traumatic growth in this population.